2018
DOI: 10.1101/258871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of an individual-based model of pneumococcal carriage for planning a randomized trial of a vaccine

Abstract: 12For encapsulated bacteria such as Streptococcus pneumoniae, asymptomatic carriage is 13 more common and longer in duration than disease, and hence is often a more convenient 14 endpoint for clinical trials of vaccines against these bacteria. However, using a carriage 15 endpoint entails specific challenges. Carriage is almost always measured as prevalence, 16 whereas the vaccine may act by reducing incidence or duration. Thus, to determine sample 17 size requirements, its impact on prevalence must first be e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Figure 3 compares VE by each of these two measures over time, during the vaccine trial. Notably, vaccine efficacy varies with time since vaccination, due to the dynamic nature of pneumococcal colonization [13]. Also interestingly, the vaccine efficacy measured post-vaccination is generally lower in a trial in a vaccinenaïve community than one in a community already using PCV13.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 3 compares VE by each of these two measures over time, during the vaccine trial. Notably, vaccine efficacy varies with time since vaccination, due to the dynamic nature of pneumococcal colonization [13]. Also interestingly, the vaccine efficacy measured post-vaccination is generally lower in a trial in a vaccinenaïve community than one in a community already using PCV13.…”
Section: Resultsmentioning
confidence: 99%
“…The result that it would be difficult to detect a small reduction in immune protection in a context of rare VT colonization was perhaps predictable by simple intuitive reasoning. However, previous work [13] has shown that pneumococcal vaccine trials with a colonization prevalence endpoint have several particularities that differ from those of more traditional vaccine trials using incidence of an acute infection as an endpoint [20,21,22,23,24]. In particular, these studies have shown that several factors complicate the interpretation of such studies:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations